A consideration of the roles of preservice teachers’ information literacy, digital literacy, and ICT self-efficacy in teaching - A Ramazani; Z. Talebi (Fanāvarī-i āmūzish, 2023)
Background and Objectives Today, technology has an important role to play in regulating society's lifestyle. People's lives are dominated by an information environment because of rapid technological progress in computers, the Internet, and smartphones. Information and communication technology (ICT) is a special branch of IT facilitating access to information. ICT can help to improve teachers' teaching experiences and prepare them for the demands of the 21st century. To be effective in the use of ICT, teachers are required to have adequate self-efficacy teaching skills. ICT self-efficacy is the concept of an individual's belief that he or she can use information and communication technologies for specific tasks. The skills of information literacy and digital literacy are required for teachers to develop their own ability to use ICT. With this consideration, the relationship between information literacy and digital literacy of preservice teachers and their ability to use ICT for learning purposes is investigated in this study.Materials and Methods: In this study, a survey research design was employed as the methodology. Data were collected using online questionnaires, and the collected data were analyzed using Confirmatory Factor Analysis (CFA). To gather data for this study, an online survey comprising two questionnaires was administered to students enrolled in teacher training programs at Farhangian University in Zanjan, Iran in 2023. One of the frameworks used as a questionnaire was rigorously developed and validated by Pinto and Markauskaite et al., while the other one was taken from the Global Framework of Reference on Digital Literacy Skills. Participants were chosen from study groups which were selected through stratified cluster sampling. Out of 1700 preservice teachers in two branches of Farhangian University (Alzahra and Shahid Beheshti), 313 preservice teachers were selected as the representatives (which was calculated based on the Morgan Table). To investigate the correlation between latent variables, survey data have been analyzed using CFA. For the evaluation of the proposed framework, structural equation modeling (SEM) was also used.Findings: The outcomes of the CFA and SEM analysis revealed that how pre-service teachers perceive their information literacy directly and positively affects their perception of digital literacy. Additionally, the results showed that pre-service teachers' perceived information literacy has a direct and positive influence on their self-confidence in using ICT for teaching, also known as ICT self-efficacy. Furthermore, the research findings indicated that the way pre-service teachers perceive their digital literacy directly and positively impacts their self-confidence in utilizing ICT for teaching. However, when compared to perceived digital literacy, the perceived information literacy of preservice teachers has a more pronounced effect on their ICT self-efficacy in the context of teaching.Conclusions: The research findings emphasize the importance of giving priority to the development of information literacy and digital literacy skills for pre-service teachers in the field of education. This is because these skills are strongly correlated with higher levels of ICT self-efficacy. The study also underscores the necessity for teacher training and professional development programs that specifically target the enhancement of information literacy and digital literacy. By focusing on these literacies, such programs have the potential to improve preservice teachers' ICT self-efficacy in teaching and enhance the effective utilization of ICT in educational settings.